THE ROLE OF FINANCIAL REPORTING QUALITY AND CORPORATE GOVERNANCE ON COMPETITION: EVIDENCE FROM MINING COMPANIES - Sekar Mayangsari; Etty Murwaningsari; Hexana Sri Lastanti (Media Riset Akuntansi, Auditing & Informasi, 2018)
The firm competition has a double quality: while it fills in as a proficient disciplinary component for firms' officials, it additionally worsens vocation concerns and increases capital market weights. This investigation analyzes the impact of financial reporting quality and corporate governanceon Competition. While from one viewpoint item showcase competition goes about as a disciplinary instrument in less aggressive enterprises, then again, it incites chiefs not to act to the greatest advantage of investors in more focused businesses. These discoveries have suggestions for the plan of corporate administration instruments and official remuneration contracts including relative execution assessment.